Hidden secrets of deformation: Impact-induced compaction within a CV chondrite - Forman, Lucy; Bland, Phil; Timms, Nicholas; Collins, G.; Davison, T.; Ciesla, F.; Benedix, Gretchen; Daly, L.; Trimby, P.; Yang, L.; Ringer, S. (Elsevier BV, 2016)
The CV3 Allende is one of the most extensively studied meteorites in worldwide collections. It is currently classified as S1—essentially unshocked—using the classification scheme of Stöffler et al. (1991), however recent modelling suggests the low porosity observed in Allende indicates the body should have undergone compaction-related deformation. In this study, we detail previously undetected evidence of impact through use of Electron Backscatter Diffraction mapping to identify deformation microstructures in chondrules, AOAs and matrix grains. Our results demonstrate that forsterite-rich chondrules commonly preserve crystal-plastic microstructures (particularly at their margins); that low-angle boundaries in deformed matrix grains of olivine have a preferred orientation; and that disparities in deformation occur between chondrules, surrounding and non-adjacent matrix grains. We find heterogeneous compaction effects present throughout the matrix, consistent with a highly porous initial material. Given the spatial distribution of these crystal-plastic deformation microstructures, we suggest that this is evidence that Allende has undergone impact-induced compaction from an initially heterogeneous and porous parent body. We suggest that current shock classifications (Stöffler et al., 1991) relying upon data from chondrule interiors do not constrain the complete shock history of a sample.